HISTORICAL PILGRIMAGE MONUMENTS OF SURKHANDARYA REGION - D. N. Abdullayeva (Journals Park Publishing, 2023)
After our country gained independence, the deep study of the history of our country and people, its truthful research on a scientific basis, impartial restoration of ancient sources, and uncovering the roots of the history of statehood became one of the main issues in the cultural and spiritual life of our republic. Taking into account the place of Islamic religion and culture in the spiritual life of society, forming and educating the thinking of young people in the Republic of Uzbekistan on the basis of enlightenment, studying and promoting the history of our religion, the heritage of our great scholars and saints, A complete study of our unique history, culture and invaluable spiritual heritage requires new scientific research.